Determinants of Student Interest to Become Entrepreneurs - Kahfi Fikrianoor; Agung Dwi Nugroho; Faishal Prahatma Ganinda; Amir Hidayatulloh (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This research aims to determine the factors that encourage student intention to become an entrepreneur. The population of this research is students in Indonesia. The research sample was undergraduate students (S1). Sampling in this research using convenience sampling. Collecting data in this research using a survey method which is carried out by distributing electronic questionnaires (google form) to respondents. The sample of this research is 126 people. Data analysis techniques in this research using Partial Least Square with the help of the WarpPLS tool. This research found that experience in entrepreneurship affects empathy, capital obligations, social support and efficacy (entrepreneurial ability). Meanwhile, the intention to become an entrepreneur is influenced by religiosity, self-efficacy, and social support. However, moral obligation and empathy have no effect on the intention to become an entrepreneur